Model Destination Branding Berbasis Preferensi Generasi Z terhadap Daya Tarik Wisata Museum di Bali - Dinar Sukma Pramesti; Made Handijaya Dewantara; Febriana Febriana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Based on the analysis of tourist visits to several museums in Bali, it is evident that the visitation numbers are still low. This study aims to develop a destination branding model based on the preferences of Generation Z tourists to increase visits to museums in Bali. This is a qualitative study, employing data collection techniques such as questionnaires, interviews, and literature reviews. Theories such as tourist gaze, storynomic tourism, and event tourism are applied to enrich understanding and develop the destination branding model. The research findings suggest the importance of integrating components such as attractions, accessibility, amenities, and ancillary to enhance tourist interest in museums in Bali. Additionally, interactive activities, event organization, informative narratives, and tourist reviews can strengthen the appeal of museums in Bali for Generation Z. The proposed destination branding model prioritizes segmentation, targeting, and positioning according to the preferences of Generation Z, with the hope of increasing museum visits and enriching visitor experiences. Although limited to domestic Generation Z tourists and museums in Bali, this study provides a significant contribution to the development of destination branding strategies relevant to the characteristics of Generation Z and can be applied in the cultural tourism context of Bali.